Case report: Imaging findings of true thymic hyperplasia at 18F-FDG PET/CT in an infant - Ren, Jiazhong; Fu, Zheng; Zhao, Yaqing (Frontiers in Oncology, 2023)
Children's true thymic hyperplasia (TTH) is rare and difficult to distinguish from other thymic tumors such as thymic teratoma and thymic liposarcoma(1). A 3-year-old girl underwent chest CT and 18F-FDG PET/CT to evaluate an anterior mediastinal mass.18F-FDG PET/CT showed a mediastinal mass showing a heterogeneous increase in FDG activity with a SUVmax of 7.1. However, pathological examination after the operation revealed true thymic hyperplasia (TTH). So far, no 18F-FDG PET/CT imaging has been reported for this disease.